2015
DOI: 10.1161/hypertensionaha.114.04354
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Activation Therapy Lowers Arterial Pressure Without Apparent Stimulation of the Carotid Bodies

Abstract: Abstract-Carotid baroreflex activation therapy produces a sustained fall in blood pressure in patients with resistant hypertension. Because the activation electrodes are implanted at the level of the carotid sinus, it is conceivable that the nearby located carotid body chemoreceptors are stimulated as well. Physiological stimulation of the carotid chemoreceptors not only stimulates respiration but also increases sympathetic activity, which may counteract the effects of baroreflex activation. The aim of this ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…These authors concluded that carotid BAT using the Rheos system involved no appreciable attendant activation of carotid body chemoreceptors during the device therapy. 16 Certainly, this is not the case concerning the approach employed in the current study in conscious rats, which deserves a thorough investigation of the respiratory changes due to the direct activation of the carotid chemoreflex.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…These authors concluded that carotid BAT using the Rheos system involved no appreciable attendant activation of carotid body chemoreceptors during the device therapy. 16 Certainly, this is not the case concerning the approach employed in the current study in conscious rats, which deserves a thorough investigation of the respiratory changes due to the direct activation of the carotid chemoreflex.…”
Section: Discussionmentioning
confidence: 88%
“…Using this experimental model, the present study shows that combined electrical stimulation of the carotid sinus and the carotid sinus nerve concomitantly activates both carotid baroreceptors and chemoreceptors, indicating that attendant carotid chemoreceptor activation blunted the hypotensive response in conscious rats. Nevertheless, it is of note that recent study of Alnima and colleagues 16 indicates no relevant carotid body coactivation with Rheos system in patients with resistant hypertension, probably because their pulse generator is implanted at the surface of each carotid sinus wall without reaching the nearby located carotid body chemoreceptors. 16 …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations